3D Printing of Flexible Electronic Devices. Issue 1 (20th November 2017) - Yang, Hui; Leow, Wan Ru; Chen, Xiaodong
Abstract: Compared to traditional, simple, planar or tubular flexible devices fabricated by spin‐coating, casting, or extrusion, 3D‐printed flexible electronic devices possess complicated geometries with precisely prescribed microarchitectures and excellent mechanical properties for satisfying all kinds of individual requirements. However, the full utilization of 3D‐printing technology to realize 3D‐printed flexible electronic devices remains limited by the flexibility and conductivity of 3D‐printing materials. To achieve 3D‐printed flexible electronic devices, the flexibility of 3D‐printed flexible devices and functionalization of conductive materials or hard silicon‐based electronic devices are combined. These 3D‐printed flexible electronic devices can be applied widely in the fields of personal wearable devices, prosthetic organs for the disabled, and human–computer interfaces. To further promote the rapid advent of 3D‐printed flexible electronic devices, the recent strategies and future developmental directions of fabricating these complex electronic devices are discussed here. Abstract : 3D‐printed flexible electronic devices possess complicated geometries and excellent mechanical properties, which enables wide applications in personal wearable devices, prosthetic organs for the disabled, and human–computer interfaces. Various 3D‐printing technologies are employed for printing flexible electronic devices through combining the flexibility of 3D‐printed devices and the functionalization of conductive materials or hard silicon‐based electronic devices.